Sodium Caseinate and Cholesterol Improve Bad Cooler Stallion Fertility - Campos, Gabriela A. [UNESP]; Garcia, Victor F.C. [UNESP]; Freitas-Dell'Aqua, Camila P. [UNESP]; Segabinazzi, Lorenzo G.T.M. [UNESP]; Maciel, Luciana F.S. [UNESP]; Alvarenga, Marco A. [UNESP]; Papa, Frederico O. [UNESP]; Dell'Aqua, José Antonio [UNESP] (Elsevier, 2020)
This study aimed to assess the effects of sodium caseinate and cholesterol to extenders used for stallion semen cooling. Two ejaculates from 19 stallions were extended to 50 million/mL in four different extenders and cooled-stored for 24 hours at 5°C. The extender 1 (E1) consisted of a commercially available skim milk–based extender. The extender 2 (E2) consisted of E1 basic formula with the milk component being replaced by sodium caseinate (20 g/L). The extender 3 (E3) consisted of E1 basic formula added to cholesterol (1.5 mg/120 million sperm). The extender 4 (E4) consisted of a combination of the E2 added to cholesterol. At 24 hours after cooling, sperm motility parameters, plasma membrane stability (PMS), and mitochondrial membrane potential were assessed. In addition, cooled semen (1 billion sperm at 5°C/24 hours) from one “bad cooler” and one “good cooler” stallions, split into four extenders was used to inseminate 30 light breed mares (30 estrous cycles/extender). Milk-based extenders (E1 and E2) had superior sperm kinetics than E3 and E4 (P < .05). Plasma membrane stabilization was significantly higher (P < .05) in E4 than E1, whereas E2 and E3 presented intermediate values (P > .05). The mitochondrial potential intensity was lower (P < .05) in E2 and E4 groups compared with E1 and E3. The good cooler stallion had high fertility (∼80%) in all extenders. However, for bad cooler stallion, E1 40% (8/20) and E2 45% (9/20) had poor fertility (P < .05) compared with E4 85% (17/20), whereas E3 55% (11/20) had intermediate value (P > .05). In conclusion, the association of sodium caseinate and cholesterol improved fertility of bad cooler stallion semen cooled for 24 hours.
Keywords: Chilled semen; Equine; Extender; Sperm